Clinical Significance of BIM Deletion Polymorphism in Non–Small-Cell Lung Cancer with Epidermal Growth Factor Receptor Mutation - Isobe, Kazutoshi (Lippincott Williams & Wilkins, 2014)
BACKGROUND: Germline alterations in the proapoptotic protein Bcl-2–like 11 (BIM) can have a crucial role in tumor response to treatment. To determine the clinical utility of detecting BIM deletion polymorphism in non–small-cell lung cancer positive for epidermal growth factor receptor (EGFR) mutation, we examined outcomes of patients with and without BIM alterations. METHODS: We studied 70 patients with EGFR mutation-positive non–small-cell lung cancer who were treated with an EGFR tyrosine kinase inhibitor between January 2008 and January 2013. BIM deletion was analyzed by polymerase chain reaction in 58 samples of peripheral blood and 24 formalin-fixed paraffin-embedded slides of surgical specimens (20 of lung tissue and four of brain tissue); both blood and tissue specimens were available for 12 patients. We retrospectively analyzed clinical characteristics, response rate, toxicity, and outcomes among patients with and without BIM deletion. RESULTS: BIM deletion was present in 13 of 70 patients (18.6%). There were no significant differences between patients with and without BIM deletion in clinical characteristics, rate of response to EGFR tyrosine kinase inhibitor, or incidence of adverse events. Patients with BIM deletion had significantly shorter progression-free survival (PFS) than those without BIM deletion (median, 227 versus 533 days; p < 0.001). Multivariate Cox regression analysis showed that BIM deletion was an independent indicator of shorter PFS (hazard ratio, 3.99; 95% confidence interval, 1.864–8.547; p < 0.001). CONCLUSIONS: Polymerase chain reaction successfully detected BIM deletion in samples of peripheral blood and formalin-fixed paraffin-embedded slides of surgical specimens. BIM deletion was the most important independent prognostic factor in shorter PFS.